(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the organization and monitoring of independent student work within the credit-module system in higher education institutions. It emphasizes the importance of systematic processes in fostering student independence, creativity, and social activity. The implementation of such processes aims to develop a new generation of specialists capable of finding their place in social and political life, and proficient in setting and solving future tasks.